L'évaluation au cours de séances d'investigation en mathématiques - Michèle Gandit (Nantes Université, 2015)
This text presents the beginning of a research project (EvaCoDice) that tries to develop formative assessment in Inquiry-Based Science Education. It is about mathematics. The EvaCoDIce project is included in a network of collaborative settings in France and is part of a European project - ASSIST-ME - about assessment within science education. The question is about how the teachers use assessment to help students (10 - 11 years old) do science. We try modelling scientific practice of the students. Formative assessment requires a change in how teachers see the process of learning and their role within it. We show some difficulties: the teachers cannot use assessment to help students, they are not still ready. We show what kind of skills and knowledge are required on the part of these teachers. A first kind of data results from an analysis of five videos. These videos were realized in classes.